Co-creation of Radical Innovations in Networks - DAchiardi, Luis (2010)
This dissertation thoroughly analyses relevant literature regarding three management topics. Additionally, it conducts a qualitative case-study research on a particular radical innovation performed by a local award winning company. The aim is to present a new alternative for managing and improving radical innovations by the interrelation of up-to-date ideas.